Main age-related cutaneous changes in men grounded on the results of ultrasonic diagnostics - Reznichenko, N. Yu.; Diudiun, A.; Reznichenko, Yu. H.; Smiian, K.; Резніченко, Наталія Юріївна; Дюдюн, А.; Резніченко, Юрій Григорович; Сміян, К. (My University, 2023)
Introduction. An extremely important task of modern medical science is to preserve the health of the population. Various age violations are found in men, such as changes in the functional activity of different systems and organs. Age-related changes have a negative influence on health state, the course of different diseases, and life quality. Materials and Methods. 120 men aged 25–64 years were examined. They were divided into four clinical groups according to the age of patients: I group – 25–34 years old, II group – 35–44 years old, III – 45–54 years old, and IV – 55–64 years old. We proposed the use of Cratal and Quercetin medications for 30 days for men from group III, and Tiocetam-Forte for 30 days for men from group IV. Ultrasound examination and dopplerography were performed. For statistical analysis, the paired Student's t-test was used. Statistical analysis was performed using STATISTICA 6.1 software. Вступ. Надзвичайно важливим завданням сучасної медичної науки є збереження здоров'я населення. У чоловіків виявляються різні вікові порушення, такі як зміни функціональної діяльності різних систем і органів. Вікові зміни негативно впливають на стан здоров'я, перебіг різних захворювань, якість життя Матеріали і методи. Обстежено 120 чоловіків віком від 25 до 64 років. За віком пацієнтів сформовано чотири клінічні групи: І група – 25–34 роки, ІІ група – 35–44 роки, ІІІ – 45–54 роки, ІV – 55–64 роки. Чоловікам ІІІ групи нами запропоновано застосування препарату «Кратал» і «Кверцетин» протягом 30 днів, а чоловікам IV групи – «Тіоцетам-форте» протягом 30 днів. Проведено ультразвукове дослідження та доплерографія. Для статистичних підрахунків використовували парний t-критерій Стьюдента. Статистичні підрахунки проводили за допомогою програмного забезпечення STATISTICA 6.1.
Основні вікові зміни шкіри у чоловіків згідно результатів ультразвукової діагностики
Резніченко Н. Ю. - https://orcid.org/0000-0002-1401-947X; Резніченко Ю. Г. - https://orcid.org/0000-0003-1534-0326.
Keywords: aging; skin; blood flow; men; старіння; шкіра; кровообіг; чоловіки